Sex, benevolence and willingness to pay for screening. Issue 10 (10th October 2016) - Whynes, David; Sach, Tracey
Abstract : Purpose: The purpose of this paper is to report the findings of a contingent valuation (CV) survey of health care services, designed to illuminate self-interest and benevolence on the part of one sex for the other. Design/methodology/approach: In a constructed scenario, men and women recorded how much they would be willing to contribute to each of three different types of cancer screening, one of which would be available only to members of the opposite sex. Findings: Over two-thirds of individuals, amongst whom men were more heavily represented, chose an identical CV for all three services. Amongst those who nominated dissimilar values, a willingness to contribute to own-sex screening coupled with an unwillingness to contribute to opposite-sex screening was more common amongst women than amongst men. Both sexes valued own-sex screening more highly than opposite-sex screening yet, compared with men, women were prepared to offer proportionately less for the latter relative to the former. In an associated person trade-off task, women were considerably less likely than men to choose opposite-sex screening at the expense of a type from which they could benefit personally. Originality/value: To date, very little research has been undertaken on differential responses to health valuation of care provision by sex. The results suggest a degree of asymmetry between the sexes, with respect to self-interest and benevolence.